IMPLEMENTASI METODE ANALITYCAL HIERARCHY PROCESS (AHP) DAN TOPSIS UNTUK PEMILIHAN KAMERA - Roby Muhammad Ikhsan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
In today’s techonologically sophisticated ,camera are an unusual item number one amoung the millennial. Camera are the property of every millennial now, The camera mirrolless is itself used to take video and picture at an excellent resolution and the result will be presented by social media user. The user have option to consider according fit the requirement. The study is conducted to recommend prospective buyer in camera selection with a consideration of photographic ,sutter speed, video resolution, sensitivity and battery resistance. Web-based decision-making system using PHP and MySQL database, by using AHP method and TOPSIS. The AHP is an analytic method for solving flexible quantitative and qualitative. AHP has an advantage on the scale of the measurement given to the structure of the hierarchy, but the AHP method has a boundary in the number of comparison used that requires a TOPSIS method, then the approach of TOPSIS has a simple but regular and logical method of steps that form a system. The result of this camera study which is recommended from the approach, alternative selection has an indirect distance from the desired distance.